2020
DOI: 10.33084/bjop.v3ispecial-1.1413
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Survey on Knowledge, Attitudes, and Practices about the COVID-19 Pandemic among Residents in North Central Nigeria

Abstract: A preliminary survey on the knowledge, attitude, and practice of the COVID-19 pandemic among residence in North Central Nigeria, was conducted. An anonymous electronic network sampling survey designed by e-survey was employed. The result showed that on the level of knowledge and practice, 76.83% opined that people may be sick for 1-14 days without developing the symptoms. On the viral transmission, 94.41% agreed that the transmission of the virus can be through direct contact with contaminated surfaces through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Therefore, it is essential that pregnant mothers and their caregivers are fully aware of the accurate facts about COVID-19 and the various preventive measures [8] . However, most studies that had assessed knowledge, attitude and the preventive measures against COVID-19 in Nigeria involved the general population and reports from these studies showed that respondents demonstrated high knowledge, positive attitude and good preventive practice among them [15][16][17][18] while the studies among the pregnant women were done in southeastern Nigeria [10,19] . This study examined the knowledge, attitude and practice of the preventive measures against coronavirus infection among pregnant women in Ekiti State University Teaching Hospital, Ado-Ekiti, south-western Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential that pregnant mothers and their caregivers are fully aware of the accurate facts about COVID-19 and the various preventive measures [8] . However, most studies that had assessed knowledge, attitude and the preventive measures against COVID-19 in Nigeria involved the general population and reports from these studies showed that respondents demonstrated high knowledge, positive attitude and good preventive practice among them [15][16][17][18] while the studies among the pregnant women were done in southeastern Nigeria [10,19] . This study examined the knowledge, attitude and practice of the preventive measures against coronavirus infection among pregnant women in Ekiti State University Teaching Hospital, Ado-Ekiti, south-western Nigeria.…”
Section: Introductionmentioning
confidence: 99%